2023
DOI: 10.1044/2023_ajslp-22-00247
|View full text |Cite
|
Sign up to set email alerts
|

A First-Person Account of Developmental Language Disorder

Abstract: Purpose: The aim of this study is to share the lived experiences of an adult with developmental language disorder (DLD) and relate her experience to the evidence base and issues in clinical practice. Method: We co-wrote a first-person account grounded in the research literature. We organized the account into six main sections: (a) the early signs of DLD; (b) diagnosis; (c) treatment; (d) the impact of DLD on family relationships, social–emotional health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…This preliminary study explores self-reported quality of life in four adolescents and one young adult with DLD, and the role of language and other risk factors in quality of life. This study addresses recent calls for research on neurodevelopmental conditions across the lifespan and research describing self-reported lived experiences of individuals with neurodevelopmental conditions (i.e., neurodiversity-informed approaches), particularly measures that are known to be associated with mental health and wellbeing (Antolini & Colizzi, 2023; Connel at al., 2014; Eigsti et al, 2022; Georgiades & Kasari, 2018; Hobson et al, 2024; e.g., Orrego et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This preliminary study explores self-reported quality of life in four adolescents and one young adult with DLD, and the role of language and other risk factors in quality of life. This study addresses recent calls for research on neurodevelopmental conditions across the lifespan and research describing self-reported lived experiences of individuals with neurodevelopmental conditions (i.e., neurodiversity-informed approaches), particularly measures that are known to be associated with mental health and wellbeing (Antolini & Colizzi, 2023; Connel at al., 2014; Eigsti et al, 2022; Georgiades & Kasari, 2018; Hobson et al, 2024; e.g., Orrego et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Measures that capture lived experiences, like self-reported quality of life indicators, can provide further insight and represent a neurodiversity-informed approach. Orrego et al (2023) underscores recent recommendations to characterize the clinical course of a condition across the lifespan. Examining quality of life in transitional phases like adolescence through young adulthood is critical because mental health and wellbeing are especially vulnerable during these developmental periods (Antolini & Colizzi, 2023).…”
mentioning
confidence: 96%
See 3 more Smart Citations